Sistema web de gestión bibliotecaria para la universidad Técnica Estatal de Quevedo - Carchi Paredes, Fausto orlando (2011)
The development of this work is the construction of a fully dynamic website in order to promote technological culture in the university community UTEQ and discover in it a way of acquiring knowledge. To carry out this research project incremental methodology was used for the stage of development and experimental methodology for the investigation stage. The website has been developed using the following tools: • • PHPDesigner 7 for PHP. • • PHP 5 • • 2.0 CodeIgniter • • MySQL 5 • • Apache 2.2 The characteristics of these technologies is that they are free and public institutions welcomes the trend to use free software for its efficiency for website development. In the design program was used: • • Artisteer 3.0 (self-generated site) • • Photoshop Once implemented the web site could be determined, the management of library material loan takes less time and less staff than it usually did, this check is performed by applying the test "T-Student" in the sampling data.